Laser-induced plasma and its applications - Chaudhary, Kashif; Haider Rizvi, Syed Zuhaib; Ali, Jalil
The laser irradiation have shown a range of applications from fabricating, melting, and evaporating nanoparticles to changing their shape, structure, size, and size distribution. Laser induced plasma has used for different diagnostic and technological applications as detection, thin film deposition, and elemental identification. The possible interferences of atomic or molecular species are used to specify organic, inorganic or biological materials which allows critical applications in defense (landmines, explosive, forensic (trace of explosive or organic materials), public health (toxic substances pharmaceutical products), or environment (organic wastes). Laser induced plasma for organic material potentially provide fast sensor systems for explosive trace and pathogen biological agent detection and analysis. The laser ablation process starts with electronic energy absorption (~fs) and ends at particle recondensation (~ms). Then, the ablation process can be governed by thermal, non-thermal processes or a combination of both. There are several types of models, i.e., thermal, mechanical, photophysical, photochemical and defect models, which describe the ablation process by one dominant mechanism only. Plasma ignition process includes bond breaking and plasma shielding during the laser pulse. Bond breaking mechanisms influence the quantity and form of energy (kinetic, ionization and excitation) that atoms and ions can acquire. Plasma expansion depends on the initial mass and energy in the plume. The process is governed by initial plasma properties (electron density, temperature, velocity) after the laser pulse and the expansion medium. During first microsecond after the laser pulse, plume expansion is adiabatic afterwards line radiation becomes the dominant mechanism of energy loss.